Thermally driven self-healing using copper nanofiber heater - Lee, Min Wook; Jo, Hong Seok; Yoon, Sam S.; Yarin, Alexander L. (AMER INST PHYSICS, 2017)
Nano-textured transparent heaters made of copper nanofibers (CuNFs) are used to facilitate accelerated self-healing of bromobutyl rubber (BIIR). The heater and BIIR layer are separately deposited on each side of a transparent flexible polyethylene terephthalate (PET) substrate. A prenotched crack on the BIIR layer was bridged due to heating facilitated by CuNFs. In the corrosion test, a cracked BIIR layer covered a steel substrate. An accelerated self-healing of the crack due to the transparent copper nanofiber heater facilitated an anti-corrosion protective effect of the BIIR layer. Published by AIP Publishing.
Keywords: TRANSPARENT ELECTRODE; NETWORKS; POLYMERS; RUBBER; LIGHT; FILMS